Reply to the comments by Pillai, S. P., George, B. G., Ray, J. S., and Kale, V. S., (GJ‐19‐0112) on Paper: "Depositional history and provenance of cratonic "Purana" basins in southern India: A multipronged geochronology approach to the Proterozoic Kaladgi and Bhima basins" by Joy et al., 2018. (18th June 2019) - Joy, Sojen; Patranabis‐Deb, Sarbani; Saha, Dilip; Jelsma, Hielke; Maas, Roland; Söderlund, Ulf; Tappe, Sebastian; van der Linde, Gert; Banerjee, Amlan; Krishnan, Unni
Abstract : We thank Patil Pillai et al. for preparing a critique on our article (Joy et al., 2018). Patil Pillai et al. contest the analytical procedure utilized for the carbonates and "geological information" documented in our research article and raise concerns on our conclusions. We hereby provide our reply to each of their comments.